A qualitative case study on handling electronic media-exposed kindergarten children: Challenges and strategies - Kamarudin, Diyana; Mohd Nasaruddin, Nur Izwa (Jurnal Pendidikan Bitara UPSI, 2020)
According to thestaronline.com on 10th August 2016, there seems to be a growing concern on the extensive usage of electronic media by young children in Malaysia. The purpose of this research was to analyze the methods adopted by schools in introducing intervention measures to these children. A qualitative case study approach was adapted for this research, with 3 participants, sampled through purposeful sampling. A triangulation method was adopted where data was collected through semi structure interviews, various levels of observations and examination of existing datas to generate qualitative themes. The themes found from this research were children’s executive function, role and responsibilities of the school, role and responsibilities of other stakeholders and the cause and effects of the interventions.The study found that awareness needs to be created among young parents on the tolerable level of gadget exposure. Wider dissemination of knowledge and information about the proper use of the electronic devices shall be another effort that need to be given attention. Diagnosing the cause early could also help children in getting early interventions by the school and parents while getting the necessary medical treatment.